Multimodal anesthesia/analgesia model in obese patients undergoing open abdominal surgery - Воротинцев, Сергій Іванович; Vorotyntsev, S; Grytcenko, S; Grynovska, M (Concord, California, 2017)
Abstract Background: Patients with concomitant obesity show increased sensitivity to opiod-induced sedation and respiratory depression. To reduce the perioperative opioid load in bariatric surgery, various multimodal anesthetic techniques are used. The purpose is to check the effectiveness of our own perioperative multimodal anesthesia/analgesia protocol for obese patients undergoing open abdominal surgery. Materials and methods: A prospective, single-centered study included 54 patients with BMI>30 kg/m2 divided into two groups. In group 1 (MAA-group, n=30), a multimodal anesthesia/analgesia protocol was used (inhaled anesthesia with sevoflurane + epidural analgesia with lidocaine/bupivacaine + low doses of ketamine + low doses of clonidine + fentanyl). In group 2 (TIVA-group, n=24) total intravenous anesthesia was performed with propofol and fentanyl, and trimeperidine was used for postoperative analgesia. Endpoint comparative values included intraoperative hemodynamic stability, extubation time, general intra- and post-operative need for opioid analgesia, mobility of patients, return to enteral feeding and degree of analgesic comfort. Statistical analysis was carried out by software Statistica for Windows version 6.0.
Keywords: obesity; abdominal surgery; multimodal anesthesia/ analgesia